De-eroticizing assault : essays on modesty, honour, and power - Kannabirān, Kalpana; Kannabiran, Vasantha (Calcutta : Stree ; Mumbai : Distributed by Popular Prakashan, 2002)
With special reference to Andhra Pradesh, India.
Keywords: Women -- Violence against -- India -- Andhra Pradesh; Feminism -- India -- Andhra Pradesh; Women -- Political activity -- India -- Andhra Pradesh; Andhra Pradesh (India) -- Politics and government